Do communal narcissists care about intelligence? Associations with high self-assessed and low objective intelligence. (June 2023) - Leniarska, Maria; Zajenkowski, Marcin; Rogoza, Radosław; Fatfouta, Ramzi
Abstract: Communal narcissism reflects the tendency to self-enhance in the communal domain. However, research indicates that the underlying self-motives in communal narcissism (e.g., the maintenance of grandiose self-views) are not uniquely communal, but also agentic. We investigated the relationship between facets of grandiose narcissism (i.e., agentic and communal narcissism) and an inherently agentic attribute – intelligence. Using two independent samples ( N 1  = 211, N 2  = 311), we found communal and agentic narcissisms were positively related to subjective (i.e., self-assessed) intelligence. However, whereas agentic narcissism was unrelated to objective intelligence, communal narcissism was negatively related to it. Finally, communal and agentic narcissism predicted overestimation of objective intelligence.